Sinergi Stakeholder dalam Mengembangkan Desa Wisata Berkelanjutan: Pemetaan dan Peran di Desa Samar Tulungagung - I Nyoman Ruja; Neni Wahyuningtyas; Khofifatu Rohmah Adi; Moh. Pebrianto; Zulfa Meutia Putri; Vian Noer Achmad Hidayat; Rihlah Khoirunnisa' Asshidiqi (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan)
Desa Samar is a village with the potential to develop into a tourist village. The village located in the Pagerwojo District, Tulungagung Regency, East Java Province has various promising natural potentials. In order to realize a Tourism Village, the role of stakeholders is certainly an important element. This study aims to identify, map, and describe the roles and relationships among stakeholders involved in the development of Samar Village Tourism. This research employs a qualitative descriptive method with data collection techniques through observation, interviews, documentation, and literature review as supporting data. The analysis technique in this study uses the stakeholder analysis method approach. The stakeholders involved are divided into primary stakeholders, key stakeholders, and secondary stakeholders. Data collection was conducted using purposive sampling to ensure the accuracy of the data collected. The research results show that the success of developing a village tourism destination is greatly determined by the collaboration among the involved stakeholders. Through stakeholder mapping in Samar Village, it was revealed that there are primary, key, and secondary stakeholders, whose interrelated roles necessitate strong commitment, coordination, and cooperation among them. Samar Village, with its various tourism potentials such as orange agro-tourism, bee farming, cattle ranching, and watermills, if managed and organized well by the related stakeholders, will become a sustainable village tourism and provide positive impacts for the community. Active participation from BUMDES, youth organizations, local government, and the local community is crucial for the successful management of these potentials. The level of active participation among stakeholders determines the sustainability of tourism in Desa Samar.